-4+3x=-6+10x

Simple and best practice solution for -4+3x=-6+10x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -4+3x=-6+10x equation:


Simplifying
-4 + 3x = -6 + 10x

Solving
-4 + 3x = -6 + 10x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-10x' to each side of the equation.
-4 + 3x + -10x = -6 + 10x + -10x

Combine like terms: 3x + -10x = -7x
-4 + -7x = -6 + 10x + -10x

Combine like terms: 10x + -10x = 0
-4 + -7x = -6 + 0
-4 + -7x = -6

Add '4' to each side of the equation.
-4 + 4 + -7x = -6 + 4

Combine like terms: -4 + 4 = 0
0 + -7x = -6 + 4
-7x = -6 + 4

Combine like terms: -6 + 4 = -2
-7x = -2

Divide each side by '-7'.
x = 0.2857142857

Simplifying
x = 0.2857142857

See similar equations:

| 12x^2y^4-3x^5+9x^3y^2=0 | | 6x+234= | | -x+33=2x+15 | | a=(3x^2y^3)(5xy^2) | | -3(1-2x)=47-x | | Solve-3(2x-9)=-3 | | 4x+6y=-132 | | 3-2x=5(3+x) | | 6+2x=2x+6 | | 9n-7=4n+8 | | 10x-50+50=-15+50 | | 23-4x=7-8x | | 12x=18-2x | | -x+1=2x+13 | | -3x-25+15x=8+15 | | -10(v+3)=-25 | | 3(r+4)-6r=-9(-3) | | -2x^2m^2(m^2-4m)= | | x+102=4x | | -7+n=3n+1 | | 75h+10= | | 15+1.50x=45 | | 14=n+8+5n | | 10x-50=-15 | | 1-5v-7v=-11 | | -9-8n=8(-6n+3)+7n | | 15x-50-5x=-15 | | -5x=54 | | 12-5=42 | | 8x-5x=8+3x+6 | | (x+102)=4x | | -24=6(-b-6) |

Equations solver categories